(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article presents an analysis of the problem of the development of creative thinking of younger schoolchildren in the context of education reform. Іt is noted that optimal conditions for the development of creative thinking of schoolchildren are provided by the education model for sustainable development. The author proves the importance of the formation of a productive educational space for the development of the creative potential of schoolchildren. Based on the analysis of theoretical positions, the features of the development of creative thinking of younger schoolchildren are analyzed. The conclusion is made about the need for targeted support of this process in the context of sustainable development education.